A comparison of ELISA and HPLC methods for determination of ochratoxin A in human blood serum in the Czech Republic - Dohnal, Vlastimil; Dvořák, Vladimír; Malíř, František; Ostrý, Vladimír; Roubal, Tomáš (Food and chemical toxicology, 2013)
Ochratoxin A (OTA) is one of the most naturally occurring fungal toxins in food. It has been detected in high concentrations in serum samples of nephropathic patients and can be applied as one of the markers of potential risk of this disease. Also, OTA can cause adverse effects on human health such as genotoxicity and is anticipated to be a potential human carcinogen. In this study, enzyme-linked immunosorbent assay (ELISA) and high performance liquid chromatography (HPLC) were applied in analysis of 115 blood serum samples of women in the child rearing age from the Czech Republic and both methods were compared. The OTA was presented in a broad range of concentrations from 0.037 to 1.130 μg/L. The outcome of ELISA and HPLC measurements were well correlated (r=0.907). However, it was observed that ELISA tend to result in underestimating the OTA level at the low serum concentrations. Both methods had the same limits of quantification of 0.050 μg/L under standard operation conditions. When OTA concentration in a sample was too low, the sample was redissolved in only 300 μL of methanol and the detection limit for HPLC was lowered to 0.030 μg OTA/L.
Keywords: Chromatography, High Pressure Liquid; Limit of Detection; Ochratoxins; limita detekce; Humans; Female; mladý dospělý; dospělí; ELISA; lidé; ochratoxiny; Germany; Enzyme-Linked Immunosorbent Assay; reprodukovatelnost výsledků; Ochratoxin A; Německo; Serum; Adult; ženské pohlaví; Reproducibility of Results; HPLC; Czech Republic; Young Adult; Česká republika; kalibrace; vysokoúčinná kapalinová chromatografie; Calibration